The Mediating Role of Cash Flow Statement Indicators in the Relationship between Stock Mispricing and Corporate Cash Holding - Ali Majid Akaleh; Hamzeh Didar; Gholamreza Mansourfar (Journal of Asset Management and Financing)
This study investigated how Tehran Stock Exchange (TSE) firms made cash holdings decisions when their stocks were mispriced in the market. The research also examined the mediating role of cash flow statement indicators in the relationship between stock mispricing and corporate cash holdings. The dataset comprised information from 106 companies listed on the TSE over an 11-year period from 2012 to 2022. The analysis was conducted using EViews and Stata software. The results of the first hypothesis test showed that stock mispricing had a positive and significant effect on a company's propensity to hold cash. The statistical models for the second and third hypotheses confirmed the mediating effects of cash flow statement indicators in the relationship between share mispricing and corporate cash holdings. However, further analysis revealed that the effects of mispricing were primarily transmitted through the channel of financing activities on a company's cash holdings decisions. The findings suggested that the firms tended to maintain higher cash reserves when their stocks were mispriced, so they could utilize these funds for investment or other purposes as needed. This underscored the importance of cash flow information in understanding how firms managed their cash holdings in response to share mispricing. The study provided insights for both corporate managers and investors regarding the drivers of corporate cash policies.Keywords: Cash Holding, Mispricing, Cash Flow, Financing.JLE: D25, D53, M41 IntroductionCorporate cash flows are a critical factor in business decision-making and financial evaluations (Mashayekh & Razani, 2021). In imperfect markets, stock mispricing can encourage firms to hold higher cash reserves to manage volatile conditions and reduce risk. Firms may maintain cash for various reasons, such as avoiding cash shortages, benefiting from tax incentives, exercising managerial discretion, and addressing agency issues (DeAngelo et al., 2010; Faulkender et al., 2019; Foroughi & Farzadi, 2014; Nanda & Vadilyev, 2023). Stock mispricing can present both opportunities and challenges, potentially leading to fluctuations in a company's cash and investment levels. From a theoretical perspective, stock mispricing can affect a firm's financial and investment decisions, prompting managers to adjust cash holdings based on the perceived misevaluation of the company's stocks. Drawing on reception theory and market timing theory, the effects of stock mispricing are primarily transmitted through a firm's financing and investment activities, which then shape its cash reserve decisions (Polk & Sapienza, 2009; Chen et al., 2021). This study investigated whether stock mispricing influenced a firm's willingness to hold cash and the specific channels, through which this effect occurred. The key research questions were: Do companies tend to increase their cash holdings in response to stock mispricing? If so, how does mispricing primarily shape a firm's desire to maintain cash reserves? Based on the theoretical foundations, the study focused on net cash flows from investment and financing activities as the potential channels, through which the effects of stock mispricing might be transmitted to the firm's cash holdings decisions.Materials & MethodsThe data pertaining to the study's variables were collected from the Tehran Stock Exchange (TSE) and Securities Exchange Organization (SEO) databases, the Rahvard Navin software, and the financial statements of the companies. The research period spanned an 11-year timeframe, covering the financial statements from 2013 to 2022. The statistical sample comprised 106 companies, representing a total of 1,166 observations. The data analysis was conducted using EViews and Stata software. By adopting a quantitative approach and leveraging post-event observations, the study ensured that the variables could not be manipulated, enhancing the reliability and validity of the findings. The use of established databases and financial statements as data sources further strengthened the credibility of the research. The analysis powered by well-regarded statistical software enabled a rigorous examination of the research hypotheses. FindingsThe analysis results of the first hypothesis indicated that stock mispricing had a positive and significant effect on a company's willingness to hold cash. This suggested that when a firm's stock value was higher than its intrinsic worth, the company tended to seize the opportunity to increase its cash reserves. The Sobel test results for the second hypothesis revealed that net cash from financing activities had a mediating effect on the relationship between mispricing and the company's desire to maintain cash. The regression analysis for the second hypothesis, in line with market timing theory, demonstrated that mispricing positively and significantly impacted net cash from financing activities. Moreover, when the mediating variable of net cash from financing activities was included in the relationship between mispricing and the company's cash holdings, the coefficient of the independent variable (mispricing) decreased slightly compared to its direct effect in the first hypothesis, but remained significant. This evidence supported the notion that, in accordance with market timing theory, companies leveraged the financing opportunities created by mispricing and tended to save and retain cash for their expenditures. The Sobel test results for the third hypothesis also aligned with the theoretical foundations, indicating that net cash from investment activities had a mediating effect on the relationship between mispricing and the company's desire to hold cash. The findings further showed that mispricing had a negative and significant impact on net cash from investment activities. This was consistent with the theoretical underpinnings and suggested that when a company's stock price was higher than its intrinsic value, the firm tended to increase its capital expenditures, leading to a negative net cash flow from investment activities. Conversely, when the stock value was lower than its real value, companies might reduce their capital expenditures, preventing cash outflows through investment activities. In some cases, the firms whose shares were priced lower than their intrinsic values might be forced to sell their capital assets due to financial difficulties and this could explain the observed negative impact. In summary, findings indicated that stock mispricing could significantly influence a company's willingness to maintain cash reserves, with the effects being primarily transmitted through the firm's financing and investment activities. Discussion & ConclusionA comparison of the Sobel test statistics for the second and third hypotheses, which were 2.504 and 2.137, respectively, indicated that the effects of stock mispricing were more pronounced through the channel of financing activities. This suggested that the company's desire to maintain cash reserves was primarily channeled through financing activities. This result highlighted the precautionary motives of the companies. The results demonstrated that these firms had paid greater attention to their financing activities and less emphasis on investment activities when their stock prices were mispriced. In other words, companies tended to accumulate cash reserves under mispricing conditions so that they could subsequently utilize these saved funds for investment or other purposes as needed. This behavior could be interpreted as a strategic response by the firms to the market timing opportunities created by stock mispricing. When a company's shares were overvalued, the firm was inclined to exploit the favorable financing conditions by increasing its cash holdings. Conversely, when the stock was undervalued, the company might scale back its investment activities to preserve cash. The mediating role of net cash from financing and investment activities in the relationship between mispricing and the firm's cash holdings further underscored the importance of these channels in the overall cash management strategy of the organizations. Companies appeared to be actively managing their cash flows and capital expenditures to capitalize on the market timing opportunities presented by stock mispricing. In conclusion, this study provided empirical evidence that stock mispricing significantly influences a company's willingness to maintain cash reserves, with the effects primarily channeled through the firm's financing and investment activities. These findings contribute to the understanding of how companies navigate the complex dynamics of stock valuation and cash management in their strategic decision-making.